2010
DOI: 10.1007/s10620-010-1210-9
|View full text |Cite
|
Sign up to set email alerts
|

Limited Low-Air Insufflation Is Optimal for Colonoscopy

Abstract: We found that limited use of low-air insufflation in the rectum and sigmoid is the procedure of choice for colonoscopic examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…It has been demonstrated that about 60 % of patients undergoing colonoscopy develop post-procedural abdominal pain 7 , which is likely due to air retention in small and large intestines with gaseous dilatation 7 . Therefore, a variety of different methods have been proposed to reduce post-procedural discomfort, including application of carbon dioxide 7 , colon decompression 5 , rectal tube placement 8 , limited air insufflation 9 , and warm water infusion 10 . It has been reported that the placement of a rectal tube after colonoscopy may improve procedure-related satisfaction and discomfort symptoms, suggesting its utility for the management of abdominal distension following colonoscopy 8 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that about 60 % of patients undergoing colonoscopy develop post-procedural abdominal pain 7 , which is likely due to air retention in small and large intestines with gaseous dilatation 7 . Therefore, a variety of different methods have been proposed to reduce post-procedural discomfort, including application of carbon dioxide 7 , colon decompression 5 , rectal tube placement 8 , limited air insufflation 9 , and warm water infusion 10 . It has been reported that the placement of a rectal tube after colonoscopy may improve procedure-related satisfaction and discomfort symptoms, suggesting its utility for the management of abdominal distension following colonoscopy 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Many "tricks" have been used to increase cecal intubation by experienced endoscopists, which include limiting air insufflation on intubation, suctioning air when encountering difficult angulation, minimizing loop formation with counter pressure, applying clockwise torque during shortening, and applying abdominal pressure. One recent randomized study that compared high-air to low-air insufflation and low-air insufflation limited to the rectum and sigmoid colon during colonoscopy showed that limited use of low-air insufflation in the rectum and sigmoid during insertion was associated with a shorter cecal intubation time, less sedation, and decreased post-procedure abdominal bloating [14].…”
Section: General Principles and Simple Maneuversmentioning
confidence: 99%
“…CAC may have a role in improving cecal intubation in a difficult or failed colonoscopy. A recent study revealed that the limited use of low-air insufflation in the rectum and sigmoid colon shortened cecal intubation time and reduced post-procedural abdominal bloating [21]. With the cap, easier anticipation of the direction in which the colonoscope should be advanced, with less air insufflation, potentially enables more comfortable examination.…”
mentioning
confidence: 99%